A single fission yeast mitotic cyclin B p34cdc2 kinase promotes both S-phase and mitosis in the absence of G1 cyclins. - Fisher, D L (1996)
Deletion of the fission yeast mitotic B-type cyclin gene cdc13 causes cells to undergo successive rounds of DNA replication. We have used a strain which expresses cdc13 conditionally to investigate re-replication. Activity of Start genes cdc2 and cdc10 is necessary and p34cdc2 kinase is active in re-replicating cells. We tested to see whether other cyclins were required for re-replication using cdc13delta. Further deletion of cig1 and puc1 had no effect, but deletion of cig2/cyc17 caused a severe delay in re-replication. Deletion of cig1 and cig2/cyc17 together abolished re-replication completely and cells arrested in G1. This, and analysis of the temperature sensitive cdc13-117 mutant, suggests that cdc13 can effectively substitute for the G1 cyclin activity of cig2/cyc17. We have characterized p56cdc13 activity and find evidence that in the absence of G1 cyclins, S-phase is delayed until the mitotic p34cdc2-p56cdc13 kinase is sufficiently active. These data suggest that a single oscillation of p34cdc2 kinase activity provided by a single B-type cyclin can promote ordered progression into both DNA replication and mitosis, and that the level of cyclin-dependent kinase activity may act as a master regulator dictating whether cells undergo S-phase or mitosis.